2020
DOI: 10.1055/s-0040-1701630
|View full text |Cite
|
Sign up to set email alerts
|

Future Ultrasound Biomarkers for Sarcopenia: Elastography, Contrast-Enhanced Ultrasound, and Speed of Sound Ultrasound Imaging

Abstract: Sarcopenia is the advanced and generalized loss of muscle mass and strength among the elderly population and is a cause of adverse outcomes. Methods used for the diagnosis of sarcopenia are either unavailable or expensive in everyday clinical settings. Ultrasound presents an inexpensive, convenient, and available method that offers advantages for the evaluation of skeletal muscle. Muscle quality will probably be the most important factor in defining sarcopenia in the future. Different features of muscle qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…As such, ultrasound measurement of rectus femoris muscle thickness has been suggested as a quick screening test for sarcopenia assessment ( 28 ). In addition, different dynamic features of muscle quality such as microcirculation, perfusion during rest and activity, as well as the muscle elasticity could be assessed using ultrasound techniques ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…As such, ultrasound measurement of rectus femoris muscle thickness has been suggested as a quick screening test for sarcopenia assessment ( 28 ). In addition, different dynamic features of muscle quality such as microcirculation, perfusion during rest and activity, as well as the muscle elasticity could be assessed using ultrasound techniques ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, US assessment of tibialis anterior muscle thickness appeared to be a promising index of muscle quantity, strength, and performance, correlating both with dynamometer and physical tests [30][31][32][33]. Other characteristics have been investigated as parameters for skeletal muscle evaluation, such as altered echogenicity, which traditionally correlates with lower muscle quality and reduced strength [34], perfusion, and also muscle elasticity [35]. Interestingly, in the context of ultrasound-based methodologies, shear wave elastography (SWE) allows abnormal passive muscle stiffness detection.…”
Section: Introductionmentioning
confidence: 99%
“…11 Furthermore, shear wave elastography (SWE) showed encouraging results in musculoskeletal system imaging to assess tendons, muscles, joints, peripheral nerves, ligaments, and soft tissue tumors. 9 Shear waves move transversely in the tissue, and their speed is higher in stiffer tissues. The differences in shear wave velocity (SWV) between tissues can be detected by the scanners, and these data are used to demonstrate color-coded images known as elastogram.…”
mentioning
confidence: 99%
“…Reproducibility and lower operator dependency are the main advantages of SWE over the other elastography techniques. 12 In this context, there were related research using brightness mode (B-mode) ultrasound combined with elastography to detect muscle changes in patients with sarcopenia, 9 Parkinson's disease, 13,14 rheumatoid arthritis, 15 stroke and so on, but few studies have explored muscle parameters, like FL and PA, obtained by two-dimensional ultrasonography in patients with diabetes. In addition, some studies 5,16 have shown that ultrasound may detect early atrophy of foot muscles in patients without DPN.…”
mentioning
confidence: 99%